Identification of Seawater Intrusion by Geoelectrical Method of Wenner Configuration in Mertasari Beach, Sanur, Denpasar - Kurniawan, Bayun; Sukrasa, I Ketut; Putra, I Ketut (BULETIN FISIKA, 2022)
Research has been conducted to determine the extent to which saltwater intrusion occurs in the area of Mertasari Beach, Sanur, Denpasar by using the Wenner configuration geoelectric method. Measurements are carried out on 5 track paths using a resistivity meter, the Naniura NDR 300HF type. The results of measurement on track paths 1 and 2 shows that saltwater intrusion has occurred with a resistivity of 0.233 ohm.m and 0.202 ohm.m. On track path 3 the saltwater intrusion has also occurred with a resistivity value of 0.268 ohm.m with the furthest intruded distance being 1013 m from track path 1. On track path 4 with a resistivity of 2.11 ohm.m, and on track path 5 with a resistivity of 1.58 ohm.m, there has not been any evidence of saltwater intrusion. Analysis results from the ground well water samples on track paths 1 and 2 have also shown a high level of salinity which indicate saltwater intrusion has occurred, while the ground well water on track path 3 is not categorized as saltwater because the distance of the well is 1041 m from the track path 1.